Treating Aggression in High-Risk Adolescent Girls: A Preliminary Evaluation - Hoffman, Sue; Cummings, Anne L.; Leschied, Alan W. (Canadian Journal of Counselling and Psychotherapy, 2007)
This pilot study examined whether aggressive responses and attitudes of high-risk adolescent girls would decrease after a group treatment that focused on the specific needs of aggressive adolescent girls. Twelve girls, aged 12-16 years from two residential facilities, participated in eight, one-hour group sessions. Results indicated a statistically significant decrease in direct aggression responses and antisocial beliefs from pretest to posttest, but no significant changes on prosocial responses or attitudes toward other girls. There were significant correlations between direct aggression and antisocial beliefs, r (11) = .49, p < .05, and between age and aggression, r (11) = -.59, p < .05, indicating that older adolescents chose less aggressive responses than younger adolescents. The results are discussed from a feminist, ecological understanding of the importance of developing gender-sensitive programming to deal effectively with adolescent female aggression.